Hydrogen Evolution Enhancement over a Cobalt-Based Schottky Interface - Yu, Hao-Zheng; Wang, Yong; Ying, Jie; Wu, Si-Ming; Lu, Yi; Hu, Jie; Hu, Ji-Song; Shen, Ling; Xiao, Yu-Xuan; Geng, Wei; Chang, Gang-Gang; Janiak, Christoph; et al. (ACS Applied Materials and Interfaces, 2019)
A proof-of-concept strategy for significant enhancement of hydrogen evolution reaction (HER) performance of transition metals via construction of a metal/semiconductor Schottky junction is presented. The decoration of low-cost commercial TiO2 nanoparticles on the surface of microscale Co dendrites causes a significant charge transfer across the Co/TiO2 Schottky interface and enhances the local electron density at the Co surface, confirmed by X-ray photoelectron spectroscopy results and density functional theory calculations. The Co/TiO2 Schottky catalyst displays superior HER activity with a turnover frequency of 0.052 s-1 and an exchange current density of 79 μA cm-2, which are about 4.3 and 4.0 times greater than that of pristine Co, respectively. Moreover, the Co/TiO2 Schottky catalyst displays excellent electrochemical durability for long-term operation in both alkaline solution and high saline solution. Theoretical calculations suggest that the Schottky junction plays an important role to optimize hydrogen adsorption free energy (ΔGH*) by tuning the electronic structure, which enhances the performance for HER of the Co/TiO2 Schottky catalyst. This study of modulating the electronic structure of the catalysts via the Schottky junction could provide valuable insights for designing and synthesizing low-cost, high-performance electrocatalysts.
Created from Fastlane, Scopus look-up
Keywords: cobalt-based electrocatalysts; DFT; electronic structure; hydrogen evolution reaction; Schottky junction